Longarm and the Howling Maniac - Evans, Tabor (Evans, Tabor. Longarm., 2010)
"High up in the snow-covered Rockies, the mining town of Sully Creek is shivering in terror. Three victims have been found with their heads in their laps, literally. Deputy U.S. Marshal Custis Long has been dispatched to bring in the killer with an ax to grind."--Page 4 of cover.